Pengembangan Media Pembelajaran Bahasa Jepang Berbasis Powerpoint Interaktif untuk Menuntun Kemampuan Berpikir Kritis Siswa - Ita Mustafa; Desak Made Sri Mardani; I Wayan Sadyana (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to develop learning media in the form of interactive powerpoint. The purpose of developing this media is to guide students' critical thinking skills. This type of research is research and development, with the MDLC (Multimedia Development Life Cycle) development model by Luther. This model consists of 6 stages, namely concept, design, material collecting, assembly, testing and distribution. Data collection was carried out using interview and questionnaire methods in the form of expert test questionnaires (media expert test, material expert test) and product trials to produce quality products. The resulting media consists of 9 themes learning material which contain new vocabulary, conversations which questions, conclusions and exercises. Based on the results of the questionnaire, the score obtained from the material expert was 87.5 (very appropriate), from media experts, namely 94.5 (very appropriate). The score obtained from the results of a limited trial questionnaire with teachers is 100 (very appropriate), while that of students is 100% (very feasible). The develop media is very suitable for use in learning Japanese.